What was a Bible for? Liturgical texts in thirteenth-century Franciscan and Dominican Bibles - Light, Laura (2019)
Many thirteenth-century portable Bibles survive with some evidence of early Franciscan or Dominican ownership. This fact is a commonplace in the scholarly literature on thirteenth-century Bibles. But it is far from obvious how these Bibles were actually used. The traditional answer is to suggest that they were tools for preachers. Although logical (and surely true in part), the manuscript evidence points in another direction. This paper explores the non-biblical texts in mendicant Bibles that are linked to liturgical use including combined Bible-Missals, Bible-Breviaries, lists of Mass readings, and marginal indications of readings for the Divine Office. The importance of Bibles adapted for liturgical use – particularly prominent in the case of mendicant Bibles – suggests a need to reorient our traditional discussions of the role of the new pocket Bible in Franciscan and Dominican life.